International heritage and historic building conservation : saving the world's past - Aygen, Zeynep (Routledge studies in heritage, 2013)
The majority of books in English on historic building conservation and heritage preservation training are often restricted to Western architecture and its origins. Consequently, the history of building conservation, the study of contemporary paradigms and case studies in most universities and within wider interest circles, predominantly in the UK, Europe, and USA focus mainly on Europe and sometimes the USA, although the latter is often excluded from European publications. With an increasingly multicultural student body in Euro-American universities and with a rising global interest in heri.